Impact of E-Procurement Implementation on Supply Chain Performance: A Case Study of Nigeria - Abubakar, Amina (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to analyze the impact of e-procurement implementation on supply chain performance: a case study of Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: E-procurement implementation in Nigeria has notably enhanced supply chain performance by streamlining processes, reducing costs, and improving transparency. It has strengthened supplier relationships, facilitated data-driven decision-making, and led to tangible benefits despite challenges such as infrastructure limitations and cybersecurity concerns. Unique Contribution to Theory, Practice and Policy: Transaction cost theory, resource dependency theory & institutional theory may be used to anchor future studies on analyze the impact of e-procurement implementation on supply chain performance: a case study of Nigeria. Provide training and capacity-building programs to enhance the technical skills and digital literacy of procurement professionals and stakeholders involved in e-procurement implementation. Advocate for the development and implementation of supportive regulatory frameworks and policies that promote e-procurement adoption and usage in Nigeria.